A Need Analysis for English Speaking and Listening Assessment Media with Web Responsive in Computer Science Faculty - Shally Amna; Dian Christina (JURNAL ARBITRER, 2021)
This study aimed at finding and analyzing the information of the ideal speaking and listening online assessment media needed in Computer Science Faculty, University of Putra Indonesia YPTK. The study used descriptive and qualitative approaches. The data instrument was a questionnaire using Likert-scale and open-questions responded by 431 students and 17 English lecturers. The result of the study showed that the students need interactive and interesting assessment web responsive while the lecturers need web responsive media which enable them to assess speaking and listening online including scoring and sending feedback. The result of the study will also be used as a matrix for developing online assessment media.